Both phenolic and non-phenolic green tea fractionsinhibit migration of cancer cells - Ean-Jeong Seo; Ching-Fen Wu; Zulfiqar Ali; Yan-Hong Wang; Shabana I. Khan; Shabana I. Khan; Larry A. Walker; Larry A. Walker; Ikhlas A. Khan; Ikhlas A. Khan; Thomas Efferth (Frontiers Media S.A., 2016)
Green tea consumption is associated with chemoprevention of many cancer types. Fresh tea leaves are rich in polyphenolic catechins, which can constitute up to 30% of the dry leaf weight. While the polyphenols of green tea have been well investigated, it is still largely unknown, whether or not non-phenolic constituents also reveal chemopreventive and anti-metastatic effects.In this study, we investigated the effects of a fraction of green tea rich in phenolic compounds (PF), a non-phenolic fraction (NPF), which contains glyceroglycolipids (GGL), and a pure glyceroglycolipid compound isolated from the non-phenolic fraction in human cancer.Dried green tea leaves were extracted and applied to a Sephadex LH-20 column. The resazurin reduction assay was used to investigate the cytotoxicity of green tea samples towards human HepG2 hepatocellular carcinoma and normal AML12 hepatocytes cells. Gene expression profiling was performed by mRNA microarray hybridization and the microarray results were validated by RT-PCR. The scratch migration assay was used to investigate the effects of green tea samples on cell migration in vitro. The changes of microtubule dynamics were observed using fluorescence microscopy.PF and NPF were prepared from methanol extract of green tea. A GGL was isolated from NPF. All three green tea samples did not show significant cytotoxic activity up to 10 µg/mL in both HepG2 and AML12 cells, whereas cytotoxicity of the control drug doxorubicin was observed with both cell lines (IC50 on AML12: 0.024 µg/mL, IC50 on HepG2: 2.103 µg/mL). We identified three sets of genes differentially expressed upon treatment with the green tea samples. The genes were associated with cytoskeleton formation, cellular movement and morphology. The correlation coefficients between mRNA expression values determined by microarray and RT-PCR were R = 0.94. HepG2 and U2OS cells treated with green tea extracts showed the delayed closures. Besides, the number of distinct tubulin filaments decreased upon treatment with green tea samples. We identified not only PF, but also glyceroglycolipids in NPF as contributing factors to the chemopreventive effects of green tea. Both PF and NPF of green tea inhibited cancer cell migration by the disassembly of microtubules, even though they were not cytotoxic.